Does changing distractor environments eliminate spatiomotor biases?. Issue 3 (21st April 2019) - Hilchey, Matthew D.; Weidler, Blaire J.; Rajsic, Jason; Pratt, Jay
ABSTRACT: This research explored how sensitive spatiomotor biases, or location-response integration effects, are to differences between visual environments. According to feature integration and episodic retrieval theories, a target's location and response are integrated to form an event representation in memory. A repetition of the prior location or target response retrieves the previously associated response or location, respectively. This leads to interference or slower responding when the retrieved event information mismatches the current event. In the four experiments here, to generate these spatiomotor biases, participants discriminated serially presented target stimuli that randomly repeated or changed location. Crucially, the visual environment of the target changed from moment-to-moment by either adding or removing distractors and placeholders. Spatiomotor biases were strong and robust across all environmental changes, with minimal to no effect of the environment on them. Thus, the spatiomotor biases generalize very well beyond the environments in which they are generated, showing that the representation of a target location and response event is not necessarily integrated with the representation of the global visual environment.